Spine classifications and severity measures - Chapman, Jens R; Dettori, Joseph R; Norvell, Daniel C (AOSpine, 2009)
A university textbook that focuses on spine disease and trauma severity measures.
Keywords: ortopedie; ukazatel závažnosti úrazu; Neurology; Orthopedics; Severity of Illness Index; stupeň závažnosti nemoci; nemoci páteře; poranění páteře; Spinal Injuries; Spinal Diseases; neurologie; Trauma Severity Indices